Pyrofomes lagerstroemiae (Polyporaceae, Basidiomycota), a new species from Hubei Province, Central China - Tang, Lu-Xin; Zhang, Yi-Zhe; Liang, Jia-Qi; Jiang, Shao-Feng; Si, Jing; Li, Hai-Jiao (Phytotaxa, 2023)
Pyrofomes lagerstroemiae sp. nov. is described and illustrated from Hubei Province, Central China, based on morphology and molecular phylogenetic analyses. The new species is characterized by greyish brown to fuscous, pileate, at first hemispherical, later triquetrous basidiomata, cinnamon buff to greyish brown pore surface, big pores (1–2.5 per mm), subglobose to broadly ellipsoid, thick-walled, truncate, smooth, IKI–, CB+ basidiospores (5–6.2 × 4–5.4 µm), and growing gregarious on Lagerstroemia indica.